Interações de cobre e fósforo em acessos de Pfaffia glomerata (Spreng.) Pedersen: efeito no crescimento e rendimento de β-ecdisona - Neis, Franciele Antonia (2013)
Pfaffia glomerata (Spregen.) Pedersen stands out as a species of great medical and commercial importance due to its major secondary metabolite β-ecdysone, which content can vary in roots under adverse conditions as nutritional stress. The aim of this study was to evaluate the effects of increasing concentrations of Cu and P in soil on the production of β-ecdysone of two accessions of P. glomerata (JB and BRA). The plants used were obtained through in vitro micropropagation and were subsequently acclimatized in hydroponics and then transplanted and grown in pots containing 4 kg of a Paleudalf soil, under glasshouse conditions. Twelve treatments were evaluated in a full factorial scheme (4x3), represented by the combination of four Cu levels (0, 20, 40 and 80 mg kg-1) and three P levels (10, 60 and 120 mg kg-1). After 100 days, the plants were harvested for evaluation of growth, nutrient content and root production of β-ecdysone. The maximum dry matter production of plants for both accesses (JB and BRA) occurred at doses of 40 mg kg-1 Cu and 10 mg kg-1 of P, and root dry matter of JB access was significantly higher when compared to BRA access. The dose of 60 mg kg-1 P influenced root growth of JB accessions at higher Cu, moreover, access roots acted as a barrier reducing the transference of the metal to the shoot. Plants of both accesses in high dose of Cu and in the presence of 10 and 120 mg kg-1 P exhibited marked growth inhibition, however the dose of 60 mg kg-1 P favored the growth of plants under conditions of metal excess in soil solution.The concentrations of β-ecdysone detected in roots of P. glomerata JB access were higher when compared to BRA access. High levels of Cu in the soil did not affect the production of β-ecdysone. However, the addition of P (120 mg kg-1) to soil reduced production of β-ecdysone.